2017
DOI: 10.18632/oncotarget.18502
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of primary versus relapse/refractory DLBCL identifies shifts in mutation spectrum

Abstract: Current understanding of the mutation spectrum of relapsed/refractory (RR) tumors is limited. We performed whole exome sequencing (WES) on 47 diffuse large B cell lymphoma (DLBCL) tumors that persisted after R-CHOP treatment, 8 matched to primary biopsies. We compared genomic alterations from the RR cohort against two treatment-naïve DLBCL cohorts (n=112). While the overall number and types of mutations did not differ significantly, we identified frequency changes in DLBCL driver genes. The overall frequency o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 42 publications
1
42
0
Order By: Relevance
“…11 In addition to comparing mutation prevalence between untreated DLBCL and rrDLBCL, some studies compared the clonal population structure and mutation burden between paired diagnostic and relapse samples. 11,12 Such analyses identified additional candidate genes whose mutation could contribute to treatment resistance, such as BCL2 and CREBBP, 11 but these results have not been independently confirmed. The genetic heterogeneity of DLBCL warrants a comprehensive study of rrDLBCL to definitively identify genes whose mutation may afford resistance to components of R-CHOP.…”
Section: Introductionmentioning
confidence: 99%
“…11 In addition to comparing mutation prevalence between untreated DLBCL and rrDLBCL, some studies compared the clonal population structure and mutation burden between paired diagnostic and relapse samples. 11,12 Such analyses identified additional candidate genes whose mutation could contribute to treatment resistance, such as BCL2 and CREBBP, 11 but these results have not been independently confirmed. The genetic heterogeneity of DLBCL warrants a comprehensive study of rrDLBCL to definitively identify genes whose mutation may afford resistance to components of R-CHOP.…”
Section: Introductionmentioning
confidence: 99%
“…NFKBIZ sSNVs were reported to be enriched in relapse specimens [30]. Two independent studies found NFKBIE to be the target of an identical frameshift 4-bp deletion in three cases [30,51]. This same frameshift deletion was also detected in the primary samples of untreated DLBCL patients [30] and in aggressive chronic lymphocytic leukemia [52].…”
Section: Common Alterations In Relapse/refractory Dlbcl and Transformmentioning
confidence: 87%
“…con rmed the data. In the end, we selected 4 articles from 1495 articles (Table 1) [4][5][6][7], and the data came from 5 independent clinical studies. We extracted the following information from eligible studies: rst author, year of publication, journal, pathological subtypes of RRDLBCL, and whole-exome sequencing results (mutated genes, mutation types, etc.)…”
Section: Study Selectionmentioning
confidence: 99%
“…At present, there are not enough large-scale studies to summarize the genetic characteristics of this particular population of RRDLBCL patients. To address this, we screened 1495 documents, from which we summarized whole-exome sequencing data from 4 studies of RRDLBCL [4][5][6][7]. By conducting an association study of whole-exome sequencing results for a total of 92 patients, we observed the most common mutations in RRDLBCL and attempted to cluster them.…”
Section: Introductionmentioning
confidence: 99%